Danger zone assessment in small-sided recreational football: providing data for consideration in relation to COVID-19 transmission. Issue 1 (11th January 2021) - Randers, Morten B; Knudsen, Nikolas Sten; Thomasen, Manuel Mounir Demetry; Panduro, Jeppe; Larsen, Malte Nejst; Mohr, Magni; Milanovic, Zoran; Krustrup, Peter; Andersen, Thomas Bull
Abstract : During the COVID-19 pandemic, physical inactivity has increased, and a wide range of sporting activities locked down, with possible long-term implications for public health. Football is the most popular sport worldwide, and recreational football training leads to broad-spectrum health effects. Football is, however, deemed a contact sport with frequent close contact important to consider during COVID-19 pandemic. Objectives: This study investigated time spent with close contact (danger zone (DZ) within 1.5 m), number of contacts and time per contact, and compared game formats in recreational small-sided football games for young and adult male football players. Methods: Movement analyses were performed on 10 Hz Global Positioning System (GPS) data collected during various small-sided football games prior to the COVID-19 outbreak. Results: Time spent in the DZ was 4.3–7.9 s/h per per cent infected players, corresponding to 34.3–114.8 s/h if one player was infected. Number of contacts with one infected player was 23.5–87.7 per hour, with an average contact time of 1.1–1.4 s, and a total number of contacts of 311–691 per hour with all players. 53%–65% of all contacts were shorter than 1 s and 77%–85% shorter than 2 s. Trivial to small effects were found for number of participants and area per player, whereas standard of play and playing with/without boards had no effect. Conclusion: This study demonstrated that during small-sided football limited time is spent within DZ and that player contacts are brief. Recreational football may therefore more appropriately be deemed as sporting activity with brief, sporadic contact.